Vitamin K2 Modulates Organelle Damage and Tauopathy Induced by Streptozotocin and Menadione in SH-SY5Y Cells - Shruti Shandilya; Kavindra Kumar Kesari; Janne Ruokolainen (MDPI AG, 2021)
Vitamin K2, known for its antioxidative and anti-inflammatory properties, can act as a potent neuroprotective molecule. Despite its action against mitochondrial dysfunction, the mechanism underlying the links between the protective effects of vitamin K2 and endoplasmic reticulum (ER) stress along with basal levels of total tau protein and amyloid-beta 42 (Aβ42) has not been elucidated yet. To understand the neuroprotective effect of vitamin K2 during metabolic complications, SH-SY5Y cells were treated with streptozotocin for 24 h and menadione for 2 h in a dose-dependent manner, followed by post-treatment of vitamin K2 for 5 h. The modulating effects of vitamin K2 on cell viability, lactate dehydrogenase release, reactive oxygen species (ROS), mitochondrial membrane potential, ER stress marker (CHOP), an indicator of unfolded protein response (UPR), inositol requiring enzyme 1 (p-IRE1α), glycogen synthase kinase 3 (GSK3α/β), total tau and Aβ42 were studied. Results showed that vitamin K2 significantly reduces neuronal cell death by inhibiting cytotoxicity and ROS levels and helps in the retainment of mitochondrial membrane potential. Moreover, vitamin K2 significantly decreased the expression of CHOP protein along with the levels and the nuclear localization of p-IRE1α, thus showing its significant role in inhibiting chronic ER stress-mediated UPR and eventually cell death. In addition, vitamin K2 significantly down-regulated the expression of GSK3α/β together with the levels of total tau protein, with a petite effect on secreted Aβ42 levels. These results suggested that vitamin K2 alleviated mitochondrial damage, ER stress and tauopathy-mediated neuronal cell death, which highlights its role as new antioxidative therapeutics targeting related cellular processes.